Constructing Micro-Landscapes: Management and Selection Practices on Microbial Communities in a Traditional Fermented Beverage - Ojeda-Linares, César Iván; Solís-García, Itzel Anayansi; Casas, Alejandro (Frontiers in Ecology and Evolution, 2022)
Colonche is a traditional beverage produced in Mexico by the fermentation of fruits of several cacti species. In the Meridional Central Plateau region of Mexico, where this study was conducted, it is mainly produced with fruits of Opuntia streptacantha; there, the producers perform spontaneous fermentation and/or fermentations through inoculums. Several factors can change the microbial community structure and dynamics through the fermentation process, but little attention has been directed to evaluate what type and extent of change the human practices have over the microbial communities. This study aims to assess the microbiota under spontaneous and inoculated fermentation techniques, the microorganisms present in the inoculums and containers, and the changes of microbiota during the process of producing colonche with different techniques. We used next-generation sequencing of the V3-V4 regions of the 16S rRNA gene and the ITS2, to characterize bacterial and fungal diversity associated with the different fermentation techniques. We identified 701 bacterial and 203 fungal amplicon sequence variants (ASVs) belonging to 173 bacterial and 187 fungal genera. The alpha and beta diversity analysis confirmed that both types of fermentation practices displayed differences in richness, diversity, and community structure. Richness of bacteria in spontaneous fermentation (0D = 136 ± 0.433) was higher than in the inoculated samples (0D = 128 ± 0.929), while fungal richness in the inoculated samples (0D = 32 ± 0.539) was higher than in spontaneous samples (0D = 19 ± 0.917). We identified bacterial groups like Lactobacillus, Leuconostoc, Pediococcus and the Saccharomyces yeast shared in ferments managed with different practices; these organisms are commonly related to the quality of the fermentation process. We identified that clay pots, where spontaneous fermentation is carried out, have an outstanding diversity of fungal and bacterial richness involved in fermentation, being valuable reservoirs of microorganisms for future fermentations. The inoculums displayed the lowest richness and diversity of bacterial and fungal communities suggesting unconscious selection on specific microbial consortia. The beta diversity analysis identified an overlap in microbial communities for both types of fermentation practices, which might reflect a shared composition of microorganisms occurring in the Opuntia streptacantha substrate. The variation in the spontaneous bacterial community is consistent with alpha diversity data, while fungal communities showed less differences among treatments, probably due to the high abundance and dominance of Saccharomyces. This information illustrates how traditional management guides selection and may drive changes in the microbial consortia to produce unique fermented beverages through specific fermentation practices. Although further studies are needed to analyze more specifically the advantages of each fermentation type over the quality of the product, our current analysis supports the role of traditional knowledge driving it and the relevance of plans for its conservation.